永磁联轴器传动力矩的一种新算法 - 王玉良; 王新昱 (Jixie chuandong)
Permanent magnet couplings transfer torque between two shafts without any mechanical contact. The calculation of transmissible torque is an important task. The relevant study for the last two decades is brief summarized. Various methods such as experiential, finite element and analytical methods are introduced and compared. The paper presents, for the first time, calculated torque equation by method of equivalent magnetic charge. This approach is proved to be a precise and easy method for the designing of magnetic couplings.